Development of Physical Training Models for U 15 Athletes in Archery - Sasmarianto, Sasmarianto; Kamaruddin, Kamaruddin; Zulrafli, Zulrafli (Universitas Majalengka, 2025)
Background: This study aims to produce Physical Training Models of athletes in 15 Archery Sports, as a reference used for athletes and coaches in conducting training. In the development of Physical Training Models for athletes u 15 Archery Sport, it provides an overview of the rubber band gym training model, body weight in order to provide a variety of physical exercises for archery athletes un 15. Methods: This research is research and development. The method in this study uses the research and development (R&D) method. Results: This research was carried out by research methods, namely: identification of potentials and problems, information collection, product design, design validation, product manufacturing, expert validation, product revision, trial, final product. Conclusion: The results of the study show that the validation results from Media Experts are 77.1%, and from the validation results of Subject Matter Experts are 87.2%. Based on small group trials, the percentage of effective and suitable for use was obtained at 77.9%, and large-scale trials were effective and feasible to use at 85.1%, with suggestions and inputs such as adding or supplementing norms to tests and measurements as well as replacing book cover images. This media is declared suitable for use as a training medium and a reference guide for archers.